Direct, uniform, and rapid Joule heating of hydrogels using alternating current - Zhengwen Li; Liang Zhong; Wenjie Liao; Bin Li; Shiping Zhu; Lei Shi (Materials & Design)
Heat up hydrogels is one of the basic topics for hydrogel engineering. Existing efforts have focused on using external heat elements to heat up hydrogels by heat conduction, whereas the possibility of hydrogels to heat up directly by themselves has been ignored. Herein, we describe Joule heating of hydrogels. The ions, which is uniformly distributed in hydrogels at the molecular level serve as heat elements. No modifications of hydrogels nor external heat elements needed, the hydrogels can heat up directly, rapidly and uniformly by directly energizing with sinusoidal alternating current of a certain frequency (∼10 kHz). In addition, we stabled heating powers through voltage modulation according to Temperature-Resistance characteristic of hydrogels. This strategy is applicable to any hydrogels theoretically, providing new opportunities for hydrogels.